Analysis of Consumer Protection Regulations Against Unlicensed Cosmetics by BPOM. Case Study: Etude House Cosmetic - Elvira Fitryani Pakpahan; Atika Sunarto; Dicky Alfredo Ginting (LEGAL BRIEF, 2022)
The purpose of this research is to analyze the regulation of consumer protection for cosmetics that are not licensed by BPOM. The research method used by the author is secondary research based on library research, laws and regulations, and related journals. The results of the study are the authors can find out that the legal protection process that has been implemented in Indonesia has been carried out properly and in accordance with existing procedures, legal remedies taken by consumers as a form of protest are more contextual because of the rapid development of technology and the role of BPOM in overcoming cosmetic products that have been circulating in the community are complex